Atributos químicos e físicos de um solo tratado com biossólido industrial e cultivado com milho - Trannin, Isabel C. de B. [UNESP]; Siqueira, José O.; Moreira, Fatima M. S. (FapUNIFESP (SciELO), 2008)
The effects of applying increasing doses of an industrial biosolid (0, 6, 12, 18 and 24 Mg ha -1 dry matter) and mineral fertilizer for two consecutive years in corn cultivation on the chemical and physical attributes of a distrophic Inceptisol under Brachiaria sp. have been evaluated in a field experiment. The chemical analysis showed that the biosolid application improved the soil fertility, especially in doses higher than 12 Mg ha -1, presenting higher organic carbon, nutrients and sodium contents, CEC, sum of bases and saturation percentage for bases and smaller pH than the control soil, with mineral fertilizer and of adjacent area, up to a depth of 0.6 m. The Cd and Pb contents were not altered significantly, while the nitrate and sodium contents increased with doses and depth, reaching 53 and 47 mg dm -3, respectively, in the 0.4-0.6 m depth layer with 24 Mg ha -1 of biosolid. The biosolid application enhanced soil aggregate stability, total porosity and microporosity and reduced soil density. The biosolid improved the fertility and the structure of soil, but its use as an agricultural input must be controlled, respecting criteria and standards so that the benefits of agricultural application overcome the risks of environmental pollution.
Chemical and physical attributes of a soil treated with an industrial biosolid and cultivated with corn
Keywords: Sewage sludge; Soil aggregate stability; Soil density; Soil fertility; Soil porosity; Brachiaria; Zea mays